Mycobacterium avium ssp. paratuberculosis in the Food Supply: A Public Health Issue - Kuenstner, Lauren; Kuenstner, John Todd (Frontiers in Public Health, 2021)
This article examines the policy implications of Mycobocterium avium subspecies paratuberculosis (MAP) as a zoonotic pathogen and the public health risks posed by the presence of MAP in food, particularly milk products. Viable MAP has been cultured from commercially pasteurized milk in the U.S. Dairy pasteurization standards and regulations are examined in light of this finding. On the basis of the precautionary principle, the authors suggest options to reduce exposure to MAP, including: 1) increased federal authority to regulate pasteurization of all dairy products, 2) modification of pasteurization standards in order to more effectively kill MAP, 3) removal of the Pasteurized Milk Ordinance (PMO) provision that allows states to override federal policy in intrastate dairy sales, and 4) creation of a mandatory Johne’s Disease Control Program. These measures would reduce human exposure to MAP and may reduce the risk of diseases associated with MAP.